Blastomycosis in 64 Wisconsin Children: Unanticipated Infection Risk and Severity in Urban Residents. Issue 9 (7th May 2021) - Hall, Jaimee M.; Havens, Peter L.; Mitchell, Errin A.; De Vela, Gabriel N.; Titus, Lauren L.; Dasgupta, Mahua; Simpson, Pippa M.; Kehl, Sue C.; Willoughby, Rodney E.; Henrickson, Kelly J.; Mitchell, Michelle L.; Huppler, Anna R.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Blastomycosis, an endemic mycosis of immunocompetent individuals, is typically seen after exposure to waterways within rural wooded regions. It is not considered a disease of urban environments. Infection can be solely pneumonic or disseminate to skin, bone or central nervous system. Unknown factors influence disease acquisition and severity in children. Methods: We analyzed acquisition risks and disease characteristics of blastomycosis in children seen at a tertiary care center from 1998 to 2018 to identify potential exposure sources, measure disease severity and assess the effect of race upon disease severity. Results: Of 64 infected children, mean age was 12.9 years, with median time to diagnosis 38.5 days. About 72% were male, 38% resided in urban counties and 50% had typical environmental exposure. Isolated pulmonary infection occurred in 33 (52%). The remainder had evidence of dissemination to skin (N = 13), bone (N = 16; 7 clinically silent) and cranium (N = 7; 3 clinically silent). Infection was moderate/severe in 19 (30%). Two children (3%) died. About 79% of children with moderate/severe disease ( P = 0.008) and 71% of urban children ( P = 0.007) lacked typical environmental exposure. Comparing children from urban counties to other residences, 63% versus 5% were black ( P < 0.001) and 71% versus 35% developed extrapulmonary dissemination ( P = 0.006). Moderate/severe disease was seen in 7/17 (42%) black children but only 12/47 (26%) children of other races ( P = 0.23). Conclusions: Blastomycosis, can be endemic in urban children in the absence of typical exposure history, have frequent, sometimes clinically silent, extrapulmonary dissemination and possibly produces more severe disease in black children.